Immune Response to Tissue‐Restricted Self‐Antigens Induces Airway Inflammation and Fibrosis Following Murine Lung Transplantation. Issue 10 (12th September 2014) - Subramanian, V.; Ramachandran, S.; Banan, B.; Bharat, A.; Wang, X.; Benshoff, N.; Kreisel, D.; Gelman, A. E.; Mohanakumar, T.
<x xml:space="preserve">Abstract</x> Immune responses against lung‐associated self‐antigens (self‐Ags) are hypothesized to play a role in the development of chronic lung graft rejection. We determined whether immune responses to lung self‐Ags, K‐alpha‐1‐tubulin (Kα1T) and Collagen V (Col‐V) in the absence of alloimmunity, could promote airway inflammation and fibrosis. Following syngeneic murine orthotopic lung transplantation (LTx) we administered antibodies (Abs) to either Kα1T or Col‐V or in combination to both of these self‐Ags. As compared to recipients of isotype control Abs, Kα1T Abs and/or Col‐V Abs‐treated recipients had marked lung graft cellular infiltration and bronchiolar fibrosis. This inflammation was also associated the accumulation of Kα1T and Col‐V‐specific interferon‐γ+ and IL‐17+ T cells. Notably, the administration of Abs to Kα1T led to cellular and humoral immune responses to Col‐V prior to development of fibrosis, and vice versa, indicating that epitope spreading can occur rapidly in an alloantigen independent manner. Collectively, these data support a model of chronic LTx rejection where the progressive loss of self‐tolerance through epitope spreading promotes airway fibrosis. Strategies that target autoreactive Abs may be useful to inhibit chronic rejection of lung grafts.